Peranan Kualitas Layanan Dan Kepuasan Pelanggan Dalam Membangun Kepercayaan Nasabah Bank Syariah - Iva Nurdiana Nurfarida; Rita Indah Mustikowati (Trunojoyo University of Madura, 2014)
There is a debate about the quality of service with trust bank syariah customers to syariah banking in applying the syariah principle, so regarded need to be researched about howquality of the service of syariah banks able to build customer satisfaction and trust. Fatmah (2007) found that affects the customer on syariah commercial banks in East Java was the quality of the service. In contrast to the research from Al – Hawari (2011) who does not find a direct relationship between the quality of services with trust. Gounaris and Venetis (2002) found that not all factors have influence on the quality of service trust. This studi was conducted to find out how the levels of trust customers of the bank syariah in applying the principles of syariah analyze the role of the quality of services of a trust customers and the role of customer satisfaction as variable mediation influence the quality of service of a trust. The research was done to the three syariah banks they were Bank Syariah Mandiri, BRI Syariah banks and Bank Syariah BNI, with samples from 150 customers by applying a technique accidental sampling method. Research variable divided into 2 namely endogenous variable that is the quality of service, while endogenous variable is satisfaction customers and trust. Data collection technique uses a questionnare that arranged in Likert sclae 5 point, while data analysis techniques use Path Analysis. The analysis shows that quality of services and not directly influence on customer trust. Professional service quality on one side of syariah bank customers will strengthen confidence, in the other side will from the creation of customer satisfaction, the satisfaction of customers will strengthen confidence of the bank syariah customers.